2016
DOI: 10.1530/jme-16-0027
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of androgen action during establishment of pregnancy

Abstract: During the establishment of pregnancy, the ovarian-derived hormones progesterone and oestradiol regulate remodelling of the endometrium to promote an environment that is able to support and maintain a successful pregnancy. Decidualisation is characterised by differentiation of endometrial stromal cells that secrete growth factors and cytokines that regulate vascular remodelling and immune cell influx. This differentiation process is critical for reproduction, and inadequate decidualisation is implicated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 92 publications
0
36
0
1
Order By: Relevance
“…There are also reasons to believe that androgens are related to preeclampsia, although their role in regulating endometrial function and vascular function in pregnancy is poorly understood [ 31 ]. Androgen receptors are expressed in the endometrium, and androgens could negatively regulate placental oxygenation and may oppose the progesterone/estrogen-mediated decrease of the resistance in the uterine arteries [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are also reasons to believe that androgens are related to preeclampsia, although their role in regulating endometrial function and vascular function in pregnancy is poorly understood [ 31 ]. Androgen receptors are expressed in the endometrium, and androgens could negatively regulate placental oxygenation and may oppose the progesterone/estrogen-mediated decrease of the resistance in the uterine arteries [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, human primary stromal cells are AR-positive and treatment of cells from proliferative phase endometrium with DHT has identified a number of androgen-regulated genes [ 28 ]. Complementary studies by Gibson et al [ 43 ], in which primary cells were stimulated to decidualise, showed local intracrine biosynthesis of androgens may play a critical role in maintenance of a decidual phenotype, with addition of flutamide reducing biosynthesis of the decidualisation marker IGFBP1 [ 43 , 59 ]. These studies complement and extend those of Cloke et al [ 60 , 61 ], who showed that AR and PR regulated distinct genomic pathways during decidualisation, consistent with a role for androgens (either local or peripheral) in regulation of fertility.…”
Section: Intracrine Steroid Biosynthesis In the Normal Endometriummentioning
confidence: 99%
“…We further demonstrated that supplementation with the androgen precursor DHEA increases biosynthesis of T and DHT and is associated with dose-dependent increases in expression of the decidualisation markers IGFBP1 and prolactin, as well as the endometrial receptivity marker SPP1 [ 40 ]. Taken together, these studies suggest both local activation and metabolism of androgens occur during decidualisation and that temporal regulation of intracrine androgen bioavailability is a critical mediator of endometrial competence during remodelling required for establishment of pregnancy [ 39 , 59 ]. These studies are of particular relevance to the impact of aging on fertility, as circulating concentrations of androgens precursors, such as DHEA and A4 as well as T and DHT decline with age [ 38 , 63 ].…”
Section: Intracrine Steroid Biosynthesis In the Normal Endometriummentioning
confidence: 99%
“…In women, the androgen receptor agonists T and dihydrotestosterone (DHT) are synthesized within peripheral tissues from DHEA by the actions of the enzymes 3ÎČ- and 17ÎČ-hydroxysteroid dehydrogenases (3BHSD, 17BHSD) and 5α-reductases. All these enzymes are expressed in the normal endometrium (9) . Whether changes in the bioavailability of DHEA determine the capacity for androgen biosynthesis in the premenopausal endometrium is not known.…”
mentioning
confidence: 99%